Determinan Perilaku Kunjungan Ulang Ibu Balita ke Posyandu di Wilayah Kerja Puskesmas Margorejo Kabupaten Pati - Emilia Yunritati Rehing; Sakundarno Adi; Antono Suryoputro (LPPM Hang Tuah Pekanbaru, 2022)
Lack of health monitoring in Posyandu is one of the causes of developmental disorders in children under five in the community. The growth and development of children at the age of toddlers as a determinant of their health in the future needs to be carried out repeatedly in order to ensure that children remain healthy and those who experience health problems can be immediately addressed, it is the responsibility of parents, especially mothers. The purpose of this study was to determine the behavioral determinants of mothers' repeat visits to the Posyandu in the Margorejo Community Health Center area. This was a quantitative study with a cross-sectional approach. Sampling used a systematic sampling of 110 respondents by filling out a questionnaire. The research variabels are intention, social support, availability of health information, personal freedom, and situation of action. Data analysis using chi-square test and logistic regression. The results showed that there was a relationship between intention, social support, personal freedom, the situation of action, and an unrelated variabel, namely the availability of health information. The conclusion of this study is that the behavior of repeat visits to the Posyandu is determined by the mother in making decisions so that she can monitor her child's growth and development at the Posyandu which has been determined every month based on this study, the variabels that influence are personal freedom and situations that allow them to act.